Göttingen State and University Library (Germany) as a Model for Successful Symbiosis of Municipal and University Library - Stepaniuk, O. L.; Kyrpyta, T. V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Objective.The article informs about Göttingen State and University Library (Germany) as about a place, where specific features of public and scientific library are taken into account. Methods. The article is based on personal impressions of a visit to the library of one of the authors. Results. The library keeps its centuries-old traditions and is modern space for individual and group work. Conclusions. The article was an attempt to describe the library’s digital and paper resources as an accumulation of experience that could be embodied in the university libraries of Ukraine.